The role of Q tRNA modification in the virulence of Leishmania mexicana - Boudová, Michala (Jihočeská univerzita, 2019)
The aim of the thesis was to indentify the orthologues of TGT1 and TGT2 genes in Leishmania mexicana and to verify the involvement of the respective gene products in the formation of Q-tRNAs in this species. Additionally, infection experiments in vitro as well as in vivo were carried out in order to test the plausible effect of Q-tRNA modification presence and/or absence on the virulence of the parasite.
The role of Q tRNA modification in the virulence of Leishmania mexicana